An introduction to Bodo script reading & writing - (:unkn) unknown (My University, 2019)
This book is An Introduction to Bodo Script - Reading and Writing consisting of 10 Units on learning about the Bodo Alphabet, Categorization of letters, Bodo Letters, Bodo Alphabet: Reading and Writing practices, Combination letter clusters, Word lists, Letters used in native and non-native words, Numerals and Basic Orthography.
Keywords: English